Saúde interface meio ambiente na localidade de Santo Antão – Santa Maria - RS - Cassol, Paulo Barrozo (2017)
This study aimed to know the residents of Santo Antão district perception in relation to the health interface environment. It was based on qualitative research, and 14 interviews realized from October to November 2016. Theoretic analysis was used where four categories emerged, to known: waste treatment centers and prisons: health and environmental reflectivity in the perception of the community of Santo Antão; The ambience and reflectivity in your health, in the context of Santo Antão community; Public Health and the use of medicinal plants as possible approach; The natural environment, the countryside as a promoting of the quality of life in the of Santo Antão community. It is concluded that the sanitation almost nonexistent, the poor roads, the work and the public transport which does not meet the local demand, the difficulties of access to specialized health treatment, point out how low the level of social development of the region, resulting in impacts on health. Endogenous actions of the location as: occupational activities, meals with products without use of pesticides, use of medicinal plants are evidence of the concern with the health through self-care; adding to the tranquility, closeness with nature and feelings of identity with the region indicate that the processes related both to health as the diseases are a result in large part of interactions between individuals and your ambience.